The Influence of Digital Marketing on Innovative Performance with Knowledge Sharing as A Mediation Variable In Five Star Hotels - Bodhi Haryanto; Ahlam Jarullah Alshoushan (International Journal Labs, 2025)
The internet penetration rate has had an average user growth rate of 62.5 % per year. Ace of 2021, the number of internet users has reached approximately 4.9 billion, and social network users were around 3.8 billion, compared to about 16 million internet users in 1995. The aim of this research is to test the influence of digital marketing on Innovative Performance, as well as test the role of knowledge sharing as a mediating variable in Corinthia Hotel Tripoli. The paradigm chosen by the researchers in this study is post-positivism. The method of this research is quantitative research. This research sample are managers and staff of five-star hotels, with a focus on the Corinthia Hotel. The number of samples used in this research was 160 respondents, managers and staff of Five Star Hotels. This study use SmartPLS software to analyze data. The results of the study show that digital marketing has a positive effect on knowledge sharing, knowledge sharing has a positive impact on innovative performance, digital marketing positively influences innovative performance and knowledge sharing mediates the relationship between digital marketing and innovative performance, which emphasizes that the impact of digital marketing on innovation is enhanced when it facilitates effective knowledge sharing.